Penguatan Kewenangan Komisi Pengawas Persaingan Usaha Lewat Putusan Mahkamah Konstitusi (Putusan Mk No.85/Puu-Xiv/2016) - A. Asmah (Kertha Wicaksana, 2021)
Business competition supervisory commission (KPPU) is a state commission formed based on the mandate of Law No. 5 of 1999 concerning the prohibition of monopolistic practices and unfair business competition. which wants healthy competition in the business sector. KPPU has the duty to enforce the law on the practice of business competition, supervise mergers and provide government policy advice. In carrying out their duties, the commission is authorized to draw up guidelines. In carrying out the tasks carried out by KPPU as the mandate of the Law to establish an efficient Indonesian economy by creating a conducive business climate, providing legal certainty so that each business actor has the same opportunity in trying and creating effectiveness and efficiency in business activities. In the formulation of the problem of the extent to which the strengthening of the Business Competition Supervisory Commission as a law enforcement agency and an independent institution established under the mandate of Law NO.5 of 1999 after the Constitutional Court's Decision becomes more directed in the enforcement of business competition law in Indonesia This research uses empirical normative research with case approaches and comparisons through existing decisions. The conclusion of the strengthening of the KPPU after the Constitutional Court's decision, as a law enforcement agency which was given the mandate in the investigation, prosecution and decision, KPPU was made as a judicial qauation institution because it could decide on a case investigated.